Building Supramolecular DNA‐Inspired Nanowires on Gold Surfaces: From 2D to 3D. (24th April 2019) - Gatto, Emanuela; Kubitzky, Sascha; Schriever, Marc; Cesaroni, Simona; Mazzuca, Claudia; Marafon, Giulia; Venanzi, Mariano; De Zotti, Marta
Abstract: Three building blocks have been designed to chemically link to a gold surface and vertically self‐assemble through thymine–adenine hydrogen bonds. Starting from these building blocks, two different films were engineered on gold surface. Film 1 consists of adenine linked to lipoic acid (Lipo–A) to covalently bind to the gold surface, and ZnTPP linked to a thymine (T–ZnTPP). Film 2 has an additional noncovalently linked layer: a helical undecapeptide analogue of the trichogin GA IV peptide, in which four glycines were replaced by four lysines to favor a helical conformation and reduce flexibility and the two extremities were functionalized with thymine and adenine to enable Lipo–A and T–ZnTPP binding, respectively. These films were characterized by electrochemical and spectroscopic techniques, and were very stable over time and when in contact with solution. Under illumination, they could generate current with higher efficiency than similar previously described systems. Abstract : Brücken bauen : Drei Bausteine wurden so entworfen, dass sie an eine Goldoberfläche binden und sich vertikal über Thymin‐Adenin‐Wasserstoffbrücken selbstorganisieren. Ausgehend von diesen Bausteinen wurden zwei unterschiedliche Filme auf einer Goldoberfläche hergestellt. Diese Filme waren stabil und konnten unter Lichteinstrahlung mit hoher Effizienz Strom erzeugen.